Analisis Bahan Tambahan Pangan, Hubungan Karakteristik Sosial Ekonomi, Pengetahuan Dan Daya Terima Terhadap Keputusan Pembelian Saus Sambal Kemasan - Dwi Noviyantini; Prita Dhyani Swamilaksita; Putri Ronitawati (Jurnal Gizi dan Kuliner, 2020)
Purchasing decisions are closely related because before making a purchase consumers make attributes as important considerations in making purchasing decisions. If the product purchased is in accordance with what is desired, the consumer will make a purchase so that it can benefit the producer. Objective: From this study is to determine the analysis of food additives, the relationship of socio-economic characteristics, knowledge and acceptability with the decision to purchase the chili sauce. Method: This study is a cross sectional study. Sampling was done by purposive sampling technique obtained a total of 110 respondents. Data collected includes socio-economic characteristics of respondents, knowledge and acceptability. Bivariate analysis using chi square statistical tests. Results: The results showed the sodium benzoate content of A Sauce 822.84 mg / kg, B  Sauce 1.035.07 mg / kg, C Sauce 567.54 mg / kg. there is a relationship between the level of education (p=0,001), income (p=0,000), level of knowledge (p=0,011), acceptance (p=0,003) with the decision to purchase chili sauce. Conclusion: Sodium Benzoate in ABC Extra Spicy Sauce and Indofood Spicy Sauce meets SNI standards, Dua Belibis Sauce exceeds SNI standards and all negative chili sauce contains Rhodamin B. coloring if consumed in excess can cause stomach cramps, stomach irritation and digestive tract irritation. Keywords: purchasing decisions, socioeconomic characteristics, knowledge, acceptability